In-field biomechanics of halfpipe snowboarding: a pilot study - Thelen, M.; Merz, C.; Gorges, T.; Goldmann, J.-P.; Donath, L.; Kersting, U. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The aim of this pilot study is to develop a method to measure the sport-specific biomechanics of the Olympic discipline of halfpipe snowboarding. An integrated fusion approach using a global navigation satellite system, inertial measurement units, and an insole system to analyse the athlete's position, movements, and forces transmitted to the board was proposed. To test the feasibility of this method a former European Cup athlete (n=1) performed 32 jumps (16 front- and backside airs) in four runs. The method provided uninterrupted measurement over extended periods of time with minimal distortion to the athlete and plausible results (COM velocity: 5.0±0.5 m/s - 13.0±0.4 m/s, back leg knee flexion: 29±2° - 64±4°, peak rear foot load: 1269±123 N). In summary, the method was feasible to capture sport-specific biomechanics of halfpipe snowboarding.